Intelligent computer mathematics : 9th International Conference, CICM 2016, Bialystok, Poland, july 25-29, 2016 /: 9th International Conference, CICM 2016, Bialystok, Poland, july 25-29, 2016. (2020) - Unknown
No abstract available